The Investigation of the Impact of Health Belief Model Based Training on Brest Self-Exam in Women Referred to Health Centers - Kheirmohammad jadgal; Iraj Zareban; Reza Faryabi; Maryam Rafie; Hadi AizadehSIUKI (Mashhad University of Medical Sciences, 2016)
Background and objective: Breast cancer is the most common cancer among women .More than 90 percent of patients are treated if diagnosed early. This study has been done to investigate the impact of Health Belief Model based training in the creation of the BSE behavior Methods: This study is a controlled intervention one performed on 180 women referred to health centers Torbat Heydaryieh which 90 people were in the intervention group and 90 people were in the control group. Before doing intervention training, a questionnaire designed based on HBM was completed by the investigating units. Then intervention training was carried out in intervention group using lecture, questions, and answers. Two month after the intervention, post tests were given using the same questionnaire. The data was analyzed by using spss 18 software, independent t-test, paired t-test and chi-square and was considered significant Results: Independent T-Test showed that before intervention, the difference between mean scores of knowledge and HBM structures of control and intervention groups was not statistically significant. But this difference was significant after the intervention Conclusion: It seems that, a training program designed based on HBM is effective to create the behavior of BSE. It is suggested educational programs Implemented  on based Health Belief Model In order to improve the performance of women. Paper Type: Research Article